An Institutional Analysis of Environmental Management in Korean Mobile Communications Industry - Dokyung Kim; Seongcheol Kim (International Telecommunications Society (ITS), 2018)
This study focused on the environmental sustainability of the mobile communications industry (MCI). Environmental sustainability in MCI can affect not only corporates in the sector but also other industries by providing solutions to cope with environmental issues. Despite the significance of environmental sustainability in MCI, there has been lack of attention from prior researchers. This study investigated the environmental issues in MCI within the integrated and holistic approach to corporate sustainable management (CSM). In addition, the environmental management (EM) of mobile network operators (MNOs) was analyzed into the framework of the institutional theory. To investigate the environmental management (EM) of mobile network operators (MNOs), we carried out a case study on three Korean mobile communications companies (SK Telecom, KT, and LG Uplus). The result of this study showed that, in terms of environmental issues, economic and environmental issues were mostly found in the MCI, and the mobile communications firms have actively coped with the issues. The MNOs' EM was relatively active, and it was confirmed that regulatory, mimetic and normative mechanisms were working simultaneously. The results of this study would provide some meaningful implications for practitioners as well as policymakers.
Keywords: 330; Corporate sustainable management; Environmental sustainability; Environmental management; Environmental issues; Institutional theory; Mobile communications industry; Mobile network operators